Service Systems Science - Kijima, Kyoichi (Springer, 2015)
The present volume illustrates a rich and promising research field in service, service systems sciences, by combining and fusing two strands of sciences: the science of service systems and systems sciences of service. The scale, complexity, and interdependence of today’s service systems have been driven to an unprecedented level by globalization, demographic changes, and technology developments, so that it is absolutely necessary now for us to cultivate a new frontier of service research.